High-power, kilojoule class laser channeling in millimeter-scale underdense plasma - Willingale, L; Nilson, P; Thomas, A; Cobble, J; Craxton, R; Maksimchuk, A; Norreys, P; Sangster, T; Scott, R; Stoeckl, C; Zulick, C; Krushelnick, K (2011)
Experiments were performed using the Omega EP laser, operating at 740 J of energy in 8 ps (90 TW), which provides extreme conditions relevant to fast ignition studies. A carbon and hydrogen plasma plume was used as the underdense target and the interaction of the laser pulse propagating and channeling through the plasma was imaged using proton radiography. The early time expansion, channel evolution, filamentation, and self-correction of the channel was measured on a single shot via this method. A channel wall modulation was observed and attributed to surface waves. After around 50 ps, the channel had evolved to show bubblelike structures, which may be due to postsoliton remnants. © 2011 American Physical Society.